Penafsiran terhadap Surah Al-Hujurat Ayat 6 dan An-Nur Ayat 15 tentang Isu Hoax Perspektif Pendekatan Maqashidi - Istiqomah, Siti Nur; Amin, Muhammad Nur; Ikhwanudin, Muhammad (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2025)
Amidst the rapid development of information and communication technology, the digital era is now faced with a serious threat in the form of the spread of fake news (hoaxes), especially those related to religious issues, which have the potential to trigger division and damage social order. With Indonesia as a country with a majority of social media users, this platform has become the main channel for the rapid spread of hoaxes. Due to this urgency, this study is crucial to examine in depth the role of the Qur'an in dealing with the hoax phenomenon. The main objective of this research is to analyze the interpretation of Surah Al-Hujurat verse 6 and An-Nur verse 15 regarding the hoax issue. This study adopts a qualitative method with a descriptive-analytical approach. The main data collection technique is literature study, collecting primary data in the form of verses of the Qur'an, as well as secondary data from the main interpretation books such as Al-Misbah, Al-Azhar, Ibnu Katsir, journals, and previous research. The results of the analysis show that these two verses fundamentally emphasize the importance of tabayyun (information verification) to protect religion (Hifzh al-Din), soul (Hifzh al-Nafs), and reason (Hifzh al-'Aql) from the negative impacts of hoaxes. In more detail, Surah Al-Hujurat verse 6 emphasizes the necessity of verifying news from people whose credibility is in doubt so as not to cause harm or regret. Meanwhile, Surah An-Nur verse 15 highlights the fatal consequences of spreading information without sufficient knowledge, which is considered a major sin in the sight of Allah. Thus, a deep understanding of these verses through the Tafsir Maqasidi Abdul Mustaqim approach offers a relevant, applicable solution for Muslims in dealing with increasingly rampant disinformation.